KEBIJAKAN PENGEMBANGAN INDUSTRI BIBIT TEBU UNGGUL UNTUK MENUNJANG PROGRAM SWASEMBADA GULA NASIONAL - Mulyono, Daru (Badan Pengkajian dan Penerapan Teknologi, 2011)
The sugarcane condition in Indonesia until now tend to decline where it is shown from the lack of sugarcane supply for fulfilling consumsion. During Dutch colony especially in 1930’s Indonesia became second big exporting of sugarcane in the world. Whereas now Indonesia become the second importing countries of sugarcane in the world. The upset condition is caused by several reasons such as: (a). Prime Bud are not available at the period time of planting, (b). Quantity of Prime Bud are not enough in order to supply the farmers need, (c). Quality of Prime Bud are not good enough according to local condition, (d). Price of Prime Bud is quite high in such away that farmers are not able to buy according to foarmers economic condition, and (e). Farmers have difficulties to access Prime Bud. Through development of sugarcane Prime Bud it will support significant incrase of sugarcane production and furthermore it will lead to sugarcane self sufficiency in Indonesia.